Brown adipose tissue: a new human organ?. Issue 2 (March 2013) - Ojha, Shalini; Birtwistle, Mark; Budge, Helen; Symonds, Michael E
Metabolism & Endocrinology Themed Meeting of the Physiological Society. Brown adipose tissue: a new human organ? The Royal Society, London, UK, 11–13 December 2012 The prevalence of obesity and overweight is increasing rapidly and functional brown adipose tissue (BAT), with its role in energy expenditure, may provide one solution. However, several key questions remain: what is the role of BAT in body metabolism, does substantial diet-induced thermogenesis exist in BAT and can it have a significant impact on total energy expenditure? Brown adipocytes are present within white adipose depots (BRITE cells) and the transcriptional control of these and classical brown adipocytes, remains an area of immense research interest. In addition, BAT has a role in lipoprotein and glucose metabolism and may play a part in aging. These, and several other burning issues around BAT, were discussed at a meeting of the Physiological Society in London, UK (11–13 December 2012).